Possible role of nanocarriers in drug delivery against cervical cancer. (1st January 2017) - Gupta, Swati; Gupta, Manish K.
ABSTRACT: Introduction: Cervical cancer is the second most common cancer and the largest cancer killer among women in most developing countries including India. Although, various drugs have been developed for cervical cancer, treatment with these drugs often results in a number of undesirable side effects, toxicity and multidrug resistance (MDR). Also, the outcomes for cervical cancer patients remain poor after surgery and chemo radiation. Methods: A literature search (for drugs and delivery systems against cervical cancer) was performed on PubMed and through Google. The present review discuss about various methods including its current conventional treatment with special reference to recent advances in delivery systems encapsulating various anticancer drugs and natural plant products for targeting towards cervical cancer. The role of photothermal therapy, gene therapy and radiation therapy against cervical cancer is also discussed. Results: Systemic/targeted drug delivery systems including liposomes, nanoparticles, hydrogels, dendrimers etc. and localized drug delivery systems like cervical patches, films, rings etc. are safer than the conventional chemotherapy which has further been proved by the several drug delivery systems undergoing clinical trials. Conclusion: Novel approaches for the aggressive treatment of cervical cancer will optimistically result in decreased side effects as well as toxicity, frequency of administration of existing drugs, to overcome MDR and to increase the survival rates.